The impact of different 75 g oral glucose tolerance test target ranges within normal limits on neonatal outcomes: A validation study - ANIK İLHAN, GÖKÇE (GALENOS YAYINCILIK, 2018)
Objective: To investigate the impact of different 75 g glucose tolerance test (OGTT) target ranges within normal limits on neonatal outcomes, thus to investigate the validity of 75 g OGTT thresholds. Materials and Methods: The normal 1-hour and 2-hour ranges of 75 g OGTT levels of 110 pregnant women with no gestational diabetes mellitus (GDM) were further divided into three different sub-groups; for the 1 hour as group 1 (< 120 mg/dL), group 2 (120-140 mg/dL), group 3 (> 140 mg/dL) and for the 2 hour as group 1 (< 120 mg/dL), group 2 (120-135 mg/dL), and group 3 (> 135 mg/dL). Results: For the 1-hour results, there was no statistically significant difference between groups in terms of age, body mass index, multiparity, neonatal hypoglycemia, hyperbilirubinemia, neonatal intensive care unit admission, birth weight, and LGT rates; however, the rate of small-for-gestational-age (SGA) infants was significantly higher in group 2 compared with those in group 3. For the 2-hour results, statistically similar results were found between the groups. Conclusion: A 2-hour 75 g OGTT has reliable threshold values for GDM screening. However, because there are still adverse neonatal outcomes in women with OGTT results below the current thresholds and the number of SGA fetuses is higher in the glucose range 120-140 mg/dL of the first hour, the validity of the 75 g OGTT thresholds still needs further investigation.
Keywords: Gestational diabetes mellitus; glucose tolerance test; neonatal outcome; screening; pregnancy; GESTATIONAL DIABETES-MELLITUS; ADVERSE PERINATAL OUTCOMES; INTERNATIONAL ASSOCIATION; DIAGNOSTIC-CRITERIA; PREGNANCY OUTCOMES; HYPERGLYCEMIA; CLASSIFICATION